PENGGUNAAN METODE PENJADWALAN BERULANG (REPETITIVE SCHEDULING METHOD) PADA PENGERJAAN PROYEK PERUMAHAN (Studi Kasus Pada Proyek Perumahan Beranda Mumbul) - Wiranata, Anak Agung; Parami Dewi, A.A Diah; Nuryawan, I Made (Jurnal Ilmiah Teknik Sipil, 2009)
Construction project is a process that manages several resources so it can achieve an aim. Planning and scheduling at construction project are related to time, cost and quality required since the balance of those three aspects is the main goal that will be pursued. There are some scheduling methods which are usually used in construction project completion. A Repetitive Scheduling Method is a kind of scheduling methods that is used for a project which has repetitive activities. This method enables showing resources management that contains of human resources, tools and materials without separating among those aspects. Applying RSM at Beranda Mumbul housing can shorten completion day from 31 weeks to 27 weeks and decrease the cost from Rp. 26.575.454,- to Rp. 25.424.127,- in a unit.
Keywords: Time, RSM, Result.